Metals in the stomach contents and brain, gonad, kidney, and liver tissues of subsistence-harvested northern sea otters (Enhydra lutris kenyoni) from Icy Strait, Alaska. (May 2021) - Brown, Kristin L.; Atkinson, Shannon; Furin, Christoff G.; Mueter, Franz J.; Gerlach, Robert
Abstract: Southeast Alaska sea otters ( Enhydra lutris ) have had a rapid rise in their population. As they feed primarily on sessile prey, they are excellent sentinels for examining metals contamination. Objectives of this study on sea otters were to determine: (1) concentrations of metals in different tissues; (2) whether metals biomagnify from stomach contents (i.e., the prey) to other tissues; (3) whether selenium and mercury concentrations indicate an overall health benefit or risk; and (4) if metals concentrations in tissues vary with body size. Brain, kidney, gonad, liver, and stomach contents were collected from freshly harvested sea otters in Icy Strait, Alaska, and analyzed for arsenic (As), cadmium (Cd), copper (Cu), lead (Pb), total mercury (THg), and selenium (Se). Metals concentrations varied significantly, and some were biomagnified, with livers and kidneys harboring the highest concentrations. Lead and arsenic appeared to be readily excreted. This study represents baseline metals concentrations to assist in monitoring the health of sea otters. Graphical abstract: Unlabelled Image Highlights: Contaminants in nonmigratory apex consumers help assess local environmental health. Kidney and liver tissues harbor highest concentrations of metals in sea otters. Mercury biomagnifies in brain, gonad, kidney, and liver tissues of sea otters. Methylmercury makes up 19–62% of total mercury in sea otter tissues. Sea otters in Southeast Alaska are healthy, with low concentrations of heavy metals.